Acute oak (Quercus infectoria) toxicosis in lambs - Eroksuz, Y.; Dabak, M.; Eroksuz, H.; Baydar, E.; Turkoglu, I.; Yilmaz, I. (Ecole Nationale Veterinaire Toulouse, 2013)
Acute intoxication caused by consumption of oak (Quercus infectoria subsp. boissieri) occurred in a flock of 92 lambs in Elazig, a province of the eastern Turkey. Four lambs had died with a history of anorexia and recumbency following introduction approximately 150 g per animal/day oak material for 10-13 days. Clinical, pathological and biochemical findings were documented in 3 lambs. The most striking biochemical changes were detected in blood urea nitrogen levels and gamma-glutamyl transferase activity. At necropsy; subcutaneous edema, mild hydrothorax, moderate ascites, severe perirenal and retroperitoneal edema, severe multifocal renal subcapsular petechiation were the major gross findings detected in all cases. Renal histopathology revealed moderate multifocal tubular cell necrosis, multifocal moderate cell swelling, multifocal tubular dilatation and hyaline cast formations. The results of this study suggest that both plant and animal based factors; namely the young age and high tannin content might contribute to the occurrence of the present toxicosis in the lambs.
Keywords: biochemical finding; clinical finding; pathological finding; oak toxicosis; Quercus infectoria; lamb